HUBUNGAN TINGKAT STRES DENGAN PERILAKU MAKAN MAHASISWA DI INDONESIA - Ikhnaton, Nadia; Dewi, Agil Dhiemitra Aulia; Fauzia, Faurina Risca (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Mental health in students can be caused by academic stress. Academic stress is a pressure that occurs caused by competition or academic demands. Students who feel stressed can experience troubled appetites. Experiencing stress will cause the release of hormones that affect eating behavior. When someone experiences stress, they tend to have unhealthy behaviors such as eating too little, overeating, eating fatty foods, or eating foods with excessive sugar. The study applied a quantitative approach using a cross-sectional design. Data collection was done through distributing a questionnaire to Indonesian students totaling 180 students as respondents. The results of the study showed a relationship between stress and 6 categories of eating behavior (low-fat eating, emotional eating, sweet snacking, cultural/environmental/healthy eating behavior, meal planning, and skipping meals). The Spearman correlation test showed a significant relationship in the category of emotional eating (p-value = 0.0001, r = 0.2874), cultural//environmental/healthy eating behavior (p-value 0.0476, r = -0.1479, skipping meals (p-value = 0.0001, r = 0.2856), in contrast, there was an insignificant relationship in the category of low-fat foods (p-value = 0.9977, r = - 0.0002), sweet snacking (p-value = 0.1625, r = 0.1045), and meal planning (p-value = 0.9051, r = 0.0090).